HERDING BEHAVIOR An Experience in Indonesian Stock Market - , Iman Taufiq Narasanto; , Prof. Dr. Eduardus Tandelilin, MBA, CWM ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Stock market is a place where investor can make profit through stock trading, and many investor prefer to buy stocks over other financial instrument because it can give significantly higher return at the expense of higher risk. Many phenomenons are occuring within stock market that influence the movement of stock price, and one of them is herding behavior, which usually viewed as making the stock market more volatile and more risky. Herding behavior is a phenomenon in which an investor is following the decision made by other investors, and it can be caused by either irrational behavior (panic or euphoria) or rational behavior (an investor take a similar action since he/she thinks the other investors must know something that he does not). Researchersâ opinion on the effect of herding on stock market is also divided